Tanggung Jawab Notaris Yang Berstatus Sebagai Tersangka Dalam Membuat Akta Otentik (PETITUM, 2023)
ABSTRACT: This research is a normative research that discusses the responsibilities of Notaries who have been named as suspects in carrying out their positions as public officials who make authentic deeds, by examining library materials or secondary data consisting of primary legal materials, even secondary law and tertiary legal materials. The results of this study indicate that, (1) Because there are no specific legal consequences in the Notary Position Law and other regulations regarding the determination of the status of a suspect against a Notary in carrying out his duties as a public official, a Notary in his status as a suspect is still obliged to carry out his duties as a public official, namely making authentic deeds. (2) Regarding the legal protection of the parties in the deed made by a Notary with a suspect status, basically the deed made by a Notary with a suspect status still has perfect evidentiary power by fulfilling the provisions of Article 1868 of the Civil Code and fulfilling the provisions of Article 16 paragraph (1) letter l of the Notary Office Law.ABSTRAK: Penelitian ini bertujuan menganalisis perlindungan hukum terhadap dokter dalam pembukaan rahasia kedokteran dalam rekam medik dan menganalisis tanggung jawab dokter dalam pembukaan rahasia kedokteran dalam rekam medik. Tipe penelitian yang digunakan oleh penulis adalah tipe penelitian normatif. Bahan hukum primer adalah bahan-bahan hukum yang mengikat terdiri dari perundang-undangan, Permenkes. Hasil dari penelitian ini adalah 1) Perlindungan hukum terhadap dokter dalam pembukaan rahasia kedokteran dalam rekam medik, diatur dalam Pasal 9 Peraturan Menteri Kesehatan Nomor 36 Tahun 2012 yaitu keadaan dimana dokter dapat membuka rahasia kedokteran dalam rekam medis tanpa persetujuan pasien sebab keadaan tertentu yang mendesak, 2) Tanggung jawab dokter dalam pembukaan rahasia kedokteran dalam rekam medik jika tidak dalam keadaan mendesak dapat diartikan dokter telah melakukan pelanggaran hukum dan juga sumpah bagi dokter, maka  sanksi dapat dijatuhkan pada dokter atas pelanggaran etikolegal.